Acute macular edema and peripapillary soft exudate after pancreas transplantation with accelerated progression of diabetic retinopathy. Issue 5 (May 2017) - Tsai, Fang‐Yi; Lau, Ling‐Ing; Li, An‐Fei; Chen, Shih‐Jen; Wang, Shin‐E; Lee, Fenq‐Lih; Liu, Catherine Jiu‐Lin; Shyr, Yi‐Ming
Abstract : Background : The effect of pancreas transplantation on diabetic retinopathy remains inconclusive. Herein, we report six patients with type 1 diabetes mellitus (DM) who underwent pancreas transplantation and developed acute macular edema and peripapillary soft exudate with rapid progression to proliferative diabetic retinopathy. Methods : In this retrospective observational study, diabetic patients who underwent pancreas transplantation in a single medical center and developed symptomatic acute macular edema and peripapillary soft exudate within 3 months after the operation were enrolled. The complete ophthalmic course and medical records of the patients were retrospectively reviewed. Diabetic retinopathy and progression following treatment after pancreas transplantation were measured. Results : Six Chinese women with type 1 DM were enrolled in this study. Mean hemoglobin (Hb) A1c was 13.4% prior to transplantation and decreased rapidly to 6.5% within 2 months postsurgery. The patients had no or mild pretransplant diabetic retinopathy and developed acute symptomatic macular edema and peripapillary soft exudate in both eyes after pancreas transplantation. All macular edema resolved either with or without treatment. Five cases progressed to proliferative diabetic retinopathy and received panretinal photocoagulation. Diabetic retinopathy remained stable in all eyes after treatment, and the visual prognosis was good, except in one eye that had macular branch retinal artery occlusion with foveal involvement. Conclusion : Acute macular edema after pancreas transplantation has a favorable treatment outcome despite rapid progression to proliferative diabetic retinopathy. High pretransplant HbA1c and abrupt blood sugar normalization may be related to the disease course.